Regional pulmonary oxygen saturations immediately after birth. (March 2022) - Gülcan Kersin, Sinem; Yaşa, Beril; Çetinkaya, Merih; Ilgın, Can; Özek, Eren; Bilgen, Hülya
Abstract: Background: Partial oxygen saturation (SpO2 ) increases within minutes during transition from the intrauterine to extrauterine life. This study aims to determine the postnatal course of pulmonary regional oxygen saturation (rSO2 ) measured by Near-Infrared Spectroscopy (NIRS). Methods: We conducted an observational study at the delivery room in infants above 35 weeks of gestation who did not need resuscitation and did not develop respiratory distress. Preductal pulse oximetry (Covidien NellcorTM) and right pulmonary apex oxygen saturation (raSO2 ) and basal oxygen saturation (rbSO2 ) (Covidien INVOSTM) were measured, starting from the postnatal third minute of life, until the 15th minute. The correlations between SpO2 and pulmonary rSO2 were analyzed. Results: Of the 110 infants included in the study, 87 were term and 23 were late preterms. The gestational age and birth weight were 38.5 ± 1.36 weeks and 3285 ± 508 g, respectively. Median (5th–95th percentile) raSO2 and rbSO2 were 79% (58–95%) and 78% (46–95%) at the third minute, respectively. The rSO2 values measured from both sides increased and reached a steady-state around postnatal 9 min, similar to SpO2 values. The pulmonary NIRS values were significantly higher for babies born by C-Section compared to babies born by vaginal delivery ( p  < 0.05). Conclusion: We found that rSO2 measurements increased within minutes in the postnatal period in late preterm and term babies without respiratory distress and reached a plateau at the postnatal 9th minute. The normal values obtained from this preliminary study may be used to predict the prognosis of cases with respiratory distress. Highlights: This study established reference ranges and percentile charts for regional pulmonary oxygenation during the first 15 minutes immediately after birth and evaluated the correlation between pulmonary NIRS and SpO2 measurements. The rSO2 values measured from both sides increased and reached a steady-state around postnatal 9 minutes, similar to SpO2 values.